Subcutaneous Angiomatoid Fibrous Histiocytoma Mimicking Metastatic Melanoma - E. Sparreboom; C. Wetzels; M. Verdijk; S. Mulder; W. Blokx (Case Reports in Pathology)
Angiomatoid fibrous histiocytoma is an uncommon soft-tissue tumor of intermediate malignancy that is often misdiagnosed initially. As there is not one immunohistochemical marker that consequently stains positive or negative for angiomatoid fibrous histiocytoma, molecular diagnostics are becoming more widely used. So far three translocations have been reported to arise in angiomatoid fibrous histiocytoma: FUS-ATF1, EWSR1-CREB1, or EWSR1-ATF1. We present a case of angiomatoid fibrous histiocytoma on the upper arm of a 40-year-old female, which was initially misdiagnosed as metastatic melanoma in a lymph node. Revision of the pathology revealed an angiomatoid fibrous histiocytoma, which was later confirmed by a EWSR1-CREB1 translocation with molecular diagnostics. Furthermore, we review the relevant literature and provide an overview of all available case reports in the past ten years. This case report illustrates the importance for pathologists of knowing the typical pathology features of AFH and integrating immunohistochemical and molecular findings in order to prevent overdiagnosis of lymph node metastasis of a malignancy.